2021
DOI: 10.1021/acs.langmuir.1c01046
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Nanoporous Silica Hydrogel by Cross-Linking of SiO2–H3BO3–Hexadecyltrimethoxysilane for Excellent Adsorption of Azo Dyes from Wastewater

Abstract: This study reports a novel cross-linking approach to fabricate the hydrothermally neutralized silica hydrogel of SiO2–H3BO3–hexadecyltrimethoxysilane by grafting alkylsilane groups onto the nanoporous silica. The synthesized silica hydrogel possessed a large specific surface area of 51.3 m2g–1 and showed excellent dye adsorption capability of cationic dyes in neutral (pH 7) and alkaline (pH 9) medium from wastewater. The colloidal electrokinetic potential analysis revealed that the outstanding adsorption effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 78 publications
4
14
0
Order By: Relevance
“…The large surface area can increase the available adsorption sites and thus improve the adsorption of dyes in aqueous solution. 35,36 The morphological feature composed of the stacked nanolayers indicates that the prepared nanolayer-constructed TiO(OH) 2 microstructures likely possess a large surface area. The nitrogen adsorption−desorption isotherm of the nanolayer-constructed TiO(OH) 2 microstructures tested at 77 K is presented in Figure 2a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large surface area can increase the available adsorption sites and thus improve the adsorption of dyes in aqueous solution. 35,36 The morphological feature composed of the stacked nanolayers indicates that the prepared nanolayer-constructed TiO(OH) 2 microstructures likely possess a large surface area. The nitrogen adsorption−desorption isotherm of the nanolayer-constructed TiO(OH) 2 microstructures tested at 77 K is presented in Figure 2a.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, the SEM images demonstrate that the prepared nanolayer-constructed TiO­(OH) 2 microstructures possess large surface areas. The large surface area can increase the available adsorption sites and thus improve the adsorption of dyes in aqueous solution. , …”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that dyes are toxic to aquatic organisms and potentially mutagenic and carcinogenic to humans. , Therefore, it is necessary to remove dyes efficiently from wastewater. To date, conventional approaches for treating dye wastewater include catalytic degradation, biodegradation, ionic exchange, membrane separation, flocculation–sedimentation, and adsorption. , Among these, adsorption is a simple, efficient, low-cost, and versatile method. …”
Section: Introductionmentioning
confidence: 99%
“…Among them, nanoparticles are regarded as rigid sites with functional ability and mechanical energy dissipation ability via adsorption–desorption of polymer chains. Examples include silver, TiO 2 , hydroxyapatite, silicate, and so forth. (2) one-dimensional nanotubes or nanofibers.…”
Section: Introductionmentioning
confidence: 99%